Studi Tentang Sensitivitas Gender - Sumbulah, Umi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2001)
Gender currently becomes a heated-discussed issue. It is often misinterpreted by people. People commonly do not realize Â·whether they keep an opinion and do something by considering gender justice. It happens a result of insufficient sensitivity on gender. This research explored how the UIIS teachers' attitude and sensitivity toward gender, which influenced their attitudes toward gender equality both in domestic roles or a social context. The result showed that the sensitivity was considered insufficient. Some efforts should be done to overcome this. Regular and temporal programs should be simultaneously done to increase their sensitivity toward gender equality.